ANALYSIS OF THE IMPORTANCE OF CHANGE MANAGEMENT AND COMPANY LEADERSHIP IN THE ERA OF CHANGE (CASE STUDY OF NOKIA COMPANY) - Sofiah, Murni; Nuri Aslami (FEB - Universitas Lampung, 2022)
This study aims to determine the importance of Change Management and Corporate Leadership in Facing the Era of Change that exists in Communication Technology Companies or Mobile Phones. The sample taken in this study is 1 Communication Technology Company, the sample was selected as a targeted case study to the NOKIA Communication Technology Company. The results show that Nokia's leadership is erratic and managers are subject to pressure and fear. There are allegations that bottom intermediaries are afraid to report real problems to leaders. When the sales report fell on target it was really infuriated Nokia executives. They accused the manager of lacking ambition, which led to low sales. Nokia's leadership at its peak was able to accept the time brought by Android and Apple but Nokia's leadership did not want to make these changes. So that makes customers switch to Android and Apple, which causes Nokia to lose its advantage.